RHETORICAL STRUCTURE OF ANNIVERSARY SPEECHES IN THE SENIOR HIGH SCHOOLS IN GHANA: A CASE OF WESLEY GIRL'S HIGH SCHOOLS AND ST. AUGUSTINE’S COLLEGE IN THE CENTRAL REGION - GYAMERA, SALAMATU; SEKYI, JOSEPH AMONOO; FENYI, DANIEL ARKOH; DADZIE, SOLOMON (Innovare Journal of Education, 2021)
The study presents a case study on the use of rhetoric in anniversary speeches of Heads of Wesley Girl’s Senior High School and St. Augustine’s College in Cape Coast in the central region of Ghana. Purposive sampling was used to sample ten (10) speeches out of twelve (12) speeches collected from the selected schools. The study employed qualitative content analysis and content analysis (these concepts are synonymous; hence no need to repeat as if they are entirely different) to analysis the data. The results show that anniversary speeches of Heads of public Senior High Schools have a six-move structure, with moves two and three used by the schools to persuade the audience and promote the schools. It was also found that the schools used the material processes to show the audience that they are working institutions by indicating what they have achieved, what they are doing and what they will do. The study also revealed that testimonials are commonly used in promotional discourse and consist of a written or spoken statement of a known or unknown endorser who praises the virtues of a product or service.